ROLE OF PROPERTY TAXES IN FINANCING TERRITORIAL SELF-GOVERNMENT UNITS (Research Bulletins of the Faculty of Economic Sciences, 2026)
This article addresses the issue of the role of property tax in financing territorial self-government units and its significance for ensuring the stability and financial independence of municipalities. The purpose of the study is to assess the importance of property tax in the structure of the own revenues of a municipality and to analyze its stability as a source of financing public tasks based on the example of the City of Koszalin. The main research problem is to determine to what extent the property tax constitutes a stable and predictable source of revenue enabling the implementation of the municipali-ty’s own tasks. For clarity, the article is divided into four main parts. The first part presents the theoretical foundations of financial independence of territorial self-government units and the importance of own revenues in the structure of the municipality’s budget. The second part is devoted to local taxes in OECD countries. The third part discusses the functions of property tax in the local economy fiscal and stimulating indicating their importance for the implementation of local economic and social policy. The last part contains an analysis of the importance of property tax in the structure of own revenues of territorial self-government, using the example of the City of Koszalin, with particular emphasis on its impact on financing public tasks. The conclusion shows that property tax is one of the most stable and predictable sources of municipal revenues, strengthening their financial independence and the ability to effectively perform public tasks.
Keywords: property tax, own revenues, local tax, financial independence, tax authority